MODIFIKASI SIMPANG BERSINYAL PADA PEMBUKAAN PINTU KELUAR-MASUK JALAN TOL - Achmad Ibnu Faishal; Daniya Tiarani; Eva Azhra Latifa (Politeknik Negeri Jakarta, 2023)
This intersection was formed as a result of the opening of toll road access, so careful planning is required to avoid any potential problems. The purpose of this study is to examine the performance of the RE Martadinata Road in Ciputat because of access to the Serpong-Cinere Toll Road, as well as the performance of the signalized intersection formed as a result of the toll access. The research process starts with field data collecting and analysis using the PKJI 2014. The examination of the 2/2TT road section's results reveals that the Ciputat and Pondok Cabe sections had the greatest saturation levels at 1,28 and 1,54, respectively. With the degree of saturation on Ciputat route 0,72 and 0,76 on Pondok Cabe route, the road is enlarging to 4/2T on the Pondok Cabe portion. The analysis of signalized junctions with the initial assumption of three phases complete and without the influence of bus pool traffic produced results with a degree of saturation in the north of 0,98 and a degree of saturation in the south of 1,11. The degree of saturation on the North half was 0,58 after the solution of changing APILL to two phases, setting green time, shifting the bus pool, and not turning right. With the influence of pool bus traffic, a saturation degree of 1,10 was obtained in the south part of 0,97, having completed the solutions for the South part of 0,60. With the influence of pool bus traffic, the Western portion of 0,96 reached a saturation level of 1,37, After completing of the West section of 0,46 solutions. The degree of saturation on the South section rises to 0,94 in the fourth year. To ensure that it still complies with the intersection's qualifying conditions, a review is required.